Osteoporosis and the risk of fracture - Science Writer Guide (South African Family Practice)
Osteoporosis is a skeletal disease characterised by low bone mass and a deterioration of the microarchitecture of bone tissue, leading to an increase in bone fragility and a greater risk of fracture. It is a life-threatening disease, with mortality following hip fracture exceeding mortality after myocardial infarction.1 For women, the risk of dying from the consequences of a hip fracture is greater than that of dying from breast cancer.2 Moreover, the morbidity associated with hip fracture, in particular, has an overwhelming impact on patients' quality of life and places an undue burden on caregivers and the healthcare system.3 The goal of osteoporosis treatment is to prevent fractures and the subsequent morbidity and mortality associated with them. More than 90% of all hip and spine fractures in elderly women result from osteoporosis.4 About 20% of patients will die in the following year as an indirect consequence of hip fracture.5 One-third of women who survive hip fracture will need constant care.6